An Examination of the Values which the Parents of Pre-school Students want their Children to Acquire - Aşikuzun, Ezgi; Kildan, A. Oğuzhan (Elsevier BV, 2014)
AbstractThe main purpose of this study is to examine the values which the parents of pre-school students want their children to acquire. The study group consists of 218 parents (109 mothers - 109 fathers) of the children receiving pre-school education in Kastamonu province in Turkey in the 2012–2013 academic year. Data have been collected by means of the “Value Ranking Form” prepared by researchers based on the content of the pre-school curriculum implemented in Turkey. This form consists of 20 values that are directly or indirectly included in the pre-school curriculum. Parents have been asked to rank these values in terms of the acquisition of their children by the order of priority. Based on this ranking, honesty comes first, respect comes second, and self-confidence comes third. Aesthetics brings up the rear.
Keywords: Parents’ Views; Pre-School Education; Value Education; 13. Climate action; 4. Education